Determination of a novel anticancer c‐Met inhibitor LS‐177 in rat plasma and tissues with a validated UPLC‐MS/MS method: application to pharmacokinetics and tissue distribution study. (4th December 2014) - Ju, Ping; Liu, Zhenzhen; Jiang, Yu; Zhao, Simin; Zhang, Lunhui; Zhang, Yuanyuan; Gu, Liqiang; Tang, Xing; Bi, Kaishun; Chen, Xiaohui
Abstract LS‐177 is a novel small‐molecule kinase inhibitor employed to interrupt the c‐Met signaling pathway. A rapid and sensitive ultraperformance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS) method was developed and validated for determination of LS‐177 in rat plasma and tissues. The biosamples were extracted by liquid–liquid extraction with methyl tert‐butyl ether and separated on a C18 column (50 × 4.6 mm, 2.6 µm) using a gradient elution mobile phase consisting of acetonitrile–0.1% formic acid water. Under the optimal conditions, the selectivity of the method was satisfactory with no endogenous interference. The intraday and interday precisions (relative standard deviation) were <10.5% and the accuracy (relative error) was from −12.5 to 12.5% at all quality control levels. Excellent recovery and negligible matrix effects were observed. Stability studies showed that LS‐177 was stable during the preparation and analytical processes. The UPLC‐MS/MS method was successfully applied to pharmacokinetic and tissue distribution studies. The results indicated that there was no significant drug accumulation after multiple‐dose oral administration of LS‐177. The tissue distribution study exhibited significant higher uptakes of LS‐177 in stomach, intestine, lung and liver among all of the tissues. The results in pharmacokinetics and tissue distribution may provide a meaningful basis for clinical application. Copyright © 2014 John Wiley & Sons, Ltd.